Kinerja Pengelolaan Sumber Air Baku Untuk Penyediaan Air Minum Kota Batam - R. Pamekas (JURNAL SUMBER DAYA AIR, 2011)
The City of Batam that is located close to Singapore has been designated as industrial, trade, tourism and seaport services of city. Hence, the internationally scale of infrastructure is needed to support their development. The availability of water sources for the City of Batam become a determinant factor for succesfulness of the City development. The city government as well as the Agency for Batam Manajemen provide a high concern to the programe of water conservation and protection of the city. However, the development of the city of Batam become a magnet to migration. Consequently, the population growth is greater that national average, and become a problem for water provision and conservation for the city of Batam. This research is aimed to model and evaluate the water preservation and conservation of water sources for water supply in Batam. This research is carried out using the system aproach and descriptif statistic method. Data is collected through instantionally survey and physical field observation and structured interview. Analysis is carried out using descriptif statistic method, and interpretation is carried out analiyically and sintetically. The research concluded that the performance of water sources management for water supply is considered adequate structurally as well as non structurally. The Indeks of community evaluation is greather than indeks of city carrying capacity. The land carrying capacity could support up to thee times the population 2010. The carrying capacity of existing water sources could only served populatian 2010. However, if all potential water reservoir is constructed and interconected completely, the carryingcapacity of reservoirs sources could served two times population 2010.